World trade and structural adjustments - Heinz Werner (Intereconomics, 1979)
The developing countries have to be involved more closely in the international division of labour if they are to be able to play their part in a New International Economic Order. Increased competition in semifinished and finished products and internal substitution processes will pose new problems for the industrialized countries and force them to consider structural readjustments in their own economies.
Keywords: 330; International Division of Labour